2018
DOI: 10.3389/fpsyt.2018.00172
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Soft Signs, Spontaneous and Treatment Emergent Extrapyramidal Syndromes in Black Africans With First Episode Schizophrenia

Abstract: Background: Very little is known about the relationship between spontaneous and treatment-induced motor syndromes in Africans with first episode schizophrenia.Objective: We investigated the association between spontaneous NSS and EPS, with treatment-induced EPS in a homogenous sample of Black Africans with first episode schizophrenia.Methods: We examined Xhosa (South Africa) and Yoruba (Nigeria) patients, using the Neurological Evaluation Scale and extrapyramidal symptoms scale before and at 3 months after exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We found that at the 4 weeks observation, there was an increase in NSS scores of patients who received haloperidol because of the development of extrapyramidal syndrome (EPS). This explained that EPS symptoms can appear at the beginning of therapy in schizophrenic patients and will affect NSS signs [18]. On the other hand, this phenomenon can also be a marker for assessing other EPS risks such as akathisia in individuals with acute schizophrenia and can be a consideration in the long-term management of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that at the 4 weeks observation, there was an increase in NSS scores of patients who received haloperidol because of the development of extrapyramidal syndrome (EPS). This explained that EPS symptoms can appear at the beginning of therapy in schizophrenic patients and will affect NSS signs [18]. On the other hand, this phenomenon can also be a marker for assessing other EPS risks such as akathisia in individuals with acute schizophrenia and can be a consideration in the long-term management of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the geographical distribution, the review included six studies from Europe [4,[25][26][27][28][29], five studies from Asia [30][31][32][33][34], two studies from Africa [35,36], one study from South America [37], and one study from North America [38]. Thirteen of these studies had employed cross-sectional design [4,26,[28][29][30][31][33][34][35][36][37] with two of which being a retrospective chart review [25,32] and the remaining two studies had employed cohort design [27,38]. The sample size of individual studies ranged from 28 [29] to 164,417 [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In PD, the cardinal diagnostic symptoms of this movement disorder (Movement Disorder Society Clinical Diagnostic Criteria for Parkinson’s Disease) involve bradykinesia/akinesia, rigidity, resting tremor and abnormalities of posture and gait [ 26 , 33 ]. In drug-naive schizophrenia, parkinsonism is characterized by these same features [ 19 24 ]. However, movement disorders in drug-naive schizophrenia can also include abnormal involuntary movements (AIM) that overlap phenomenologically with what would be described as tardive dyskinesia in schizophrenia patients who have received long-term treatment with antipsychotics [ 12 , 19 24 ] and dyskinesia in PD patients who have received long-term treatment with L-dopa [ 26 ].…”
Section: Pathobiological Challengesmentioning
confidence: 99%
“…In drug-naive schizophrenia, parkinsonism is characterized by these same features [ 19 24 ]. However, movement disorders in drug-naive schizophrenia can also include abnormal involuntary movements (AIM) that overlap phenomenologically with what would be described as tardive dyskinesia in schizophrenia patients who have received long-term treatment with antipsychotics [ 12 , 19 24 ] and dyskinesia in PD patients who have received long-term treatment with L-dopa [ 26 ]. Furthermore, parkinsonism and AIM can occasionally cooccur in patients with drug-naive schizophrenia; in such instances, it appears that while parkinsonism is evident primarily in peripheral regions, AIM have a primarily orofacial topography [ 19 24 ].…”
Section: Pathobiological Challengesmentioning
confidence: 99%
See 1 more Smart Citation